Fluoride Exposure and Salivary Glands: How Is Glandular Morphology Susceptible to Long-Term Exposure? A Preclinical Study - Matos-Sousa, José Mário; Bittencourt, Leonardo Oliveira; Ferreira, Maria Karolina Martins; dos Santos, Vinicius Ruan Neves; Balbinot, Karolyny Martins; Alves-Júnior, Sérgio; Pinheiro, João de Jesus Viana; Charone, Senda; Pessan, Juliano Pelim [UNESP]; Lima, Rafael Rodrigues (MDPI, 2022)
Despite a strong body of evidence attesting to the effectiveness of fluoride (F) in preventing and controlling caries, some studies have sought to investigate the influence of F exposure on the salivary glands, organs that are essential for the maintenance of cavity homeostasis through salivary production, finding that exposure to F can cause biochemical and proteomic changes. Thus, this study aimed to investigate the morphological effects of prolonged exposure to F on the salivary glands of mice, at concentrations that would correspond to optimally fluoridated water (suitable for human consumption) and to fluorosis-endemic regions. Twenty-four male mice (Mus musculus) were divided into three groups, according to F levels in the drinking water: 0 (control), 10, or 50 mg F/L, with an exposure period of 60 days. The glands were morphometrically analyzed for the total acinar area, parenchyma area, and stromal area, as well as for the immunohistochemical analysis of myoepithelial cells. The results showed that prolonged exposure to F at 10 mg F/L did not promote significant changes in the morphometry of the salivary glands of mice, which reinforces the safety of the chronic use of F in low doses.
Keywords: fluoride; salivary glands; sodium fluoride